A re‐examination of the BIS/BAS scales: Evidence for BIS and BAS as unidimensional scales - Maack, Danielle J. (Int J Methods Psychiatr Res, 2018)
OBJECTIVES: Carver and White's behavioral inhibition system and behavioral activation system (BIS/BAS) scales are the most widely used to assess constructs of the revised reinforcement sensitivity theory. This study provides a re‐examination of the latent structure of the original BIS/BAS scales. METHODS: The interpretability of the three purported BAS subfactors relative to a “general behavioral activation” factor was assessed using Schmid–Leiman and standard confirmatory factor analysis. Regarding the BIS scale, comparisons were made between (a) Carver and White's unidimensional BIS model, (b) Johnson, Turner, and Iwata's 2‐factor BIS model, (c) Heym, Ferguson, and Lawrence's alternative 2‐factor BIS model, and (d) a modified Heym et al. model (unidimensional) controlling for method effects of reverse‐scored items. RESULTS: Results revealed the majority of variance of individual BAS items was accounted for by a common, general BAS dimension. Additionally, for the BIS scale, results of the χ(2) difference statistical test supporting the 1‐factor model, as well as the noted theoretical and psychometric difficulties in interpreting a multifactor BIS scale, provide converging support that BIS items actually represent a single, unidimensional factor. CONCLUSIONS: The collective results suggested that the BIS and BAS scales should be conceptualized as separate unidimensional measures, which is consistent with theory behind the original development.